Polygamy and family member relationship on Guinean family business succession planning - Oury Bailo, Diallo Oury; Hassan, Arif; Mhd. Sarif, Suhaimi; Abdullah Othman, Anwar Hasan (Emerald Publishing Limited, 2023)
Purpose – The aim of the paper is to identify the key factors that affect Guinean family business (FB) succession planning. The study also evaluates the impact of these factors on the succession planning process to ensure business continuity. Design/methodology/approach – This descriptive quantitative research is based on a survey of 383 family businesses FBs in Conakry, the capital city of Guinea. The structural equation model (SEM) was used to analyze and validate the model featuring factors that influence family business FB succession planning (FBSP). The Theory of Stewardess and the Theory of FB Rivalry have been employed in the study. Findings – While the incumbent attributes, firm attributes, and estate tax were revealed to have no significant influence on succession planning, the successor attributes and the family relationship significantly affected succession planning. Besides, undesirable domestic relationships among children of different mothers from polygamous families had an indirect impact on business succession planning. Research limitations/implications – The limitations of the study include the population of the FBs being restricted only to those located in Conakry, the capital city. The study did not consider other regions and cities of Guinea. Besides, the grouping of attributes or characteristics was problematic, and studying each attribute separately as an independent variable would be much better. Finally, the limited literature and available data on Guinean FBs in general and succession planning generalize the findings to be done cautiously. Therefore, more studies are needed on FB succession in the country to further confirm these findings. Social implications – The study may help ensure social solidarity based on the findings of factors associated to polygamous families in relation to businesses. Originality/value – Few studies have been done on FBs in Conakry. Besides, putting attributes or characteristics into categories has been presented. Moreover, there is inadequate relevant literature and data on Guinean FBSP. Considering these limitations, the generalization of the findings should be done with caution. Therefore, this study touched on the issue of family business succession in Guinea which substantiates the findings.